When Helpers Go Above and Beyond: Development and Characterization of Cytotoxic CD4+ T Cells - Hoeks, Cindy; Duran, Gayel; Hellings, Niels; Broux, Bieke (Frontiers in Immunology, 2022)
Once regarded as an experimental artefact, cytotoxic CD4+ T cells (CD4 CTL) are presently recognized as a biologically relevant T cell subset with important functions in anti-viral, anti-tumor, and autoimmune responses. Despite their potentially large impact on their micro-environment, the absolute cell counts of CD4 CTL within the peripheral circulation are relatively low. With the rise of single cell analysis techniques, detection of these cells is greatly facilitated. This led to a renewed appraisal of CD4 CTL and an increased insight into their heterogeneous nature and ontogeny. In this review, we summarize the developmental path from naïve CD4+ T cells to terminally differentiated CD4 CTL, and present markers that can be used to detect or isolate CD4 CTL and their precursors. Subsets of CD4 CTL and their divergent functionalities are discussed. Finally, the importance of local cues as triggers for CD4 CTL differentiation is debated, posing the question whether CD4 CTL develop in the periphery and migrate to site of inflammation when called for, or that circulating CD4 CTL reflect cells that returned to the circulation following differentiation at the local inflammatory site they previously migrated to. Even though much remains to be learned about this intriguing T cell subset, it is clear that CD4 CTL represent interesting therapeutic targets for several pathologies.